PENGARUH BEBAN BIAYA DAN PENDAPATAN TERHADAP PERTUMBUHAN LABA PT PEGADAIAN DENGAN GROSS PROFIT MARGIN SEBAGAI VARIABEL INTERVENING DI CABANG BESUKI KABUPATEN SITUBONDO TAHUN 2019-2021 - Mahila, Laely Septy Izza; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The purpose of this study is to investigate the influence of cost burden and income on profit growth of PT Pegadaian with Gross Profit Margin as an intervening variable at Besuki Branch, Situbondo, for the years 2019-2021. The population for this research comprises reports accessible for 5 years from 2018 to 2022 (5 x 12 months = 60 data) at PT Pegadaian Besuki branch. The sampling technique used ;in the study is purposive sampling, resulting in a total of 36 data points within a 3-year period (2019, 2020, 2021) x 12 months = 36 data points. The sampling technique employed is purposive sampling. Data analysis and hypothesis testing in this research were conducted using the Structural Equation Model – Partial Least Square (PLS-SEM). The results of hypothesis testing for direct effects using Smart PLS 3.0 indicate that cost burden has a significant negative effect on gross profit margin, income has a significant negative effect on gross profit margin, cost burden has a positive but not significant effect on profit growth, cost burden has a significant negative effect on profit growth, and gross profit margin has a significant negative effect on profit growth. The results of hypothesis testing for indirect effects show that the cost burden variable has a significant negative effect on profit growth through gross profit, and income has a significant negative effect on profit growth through Gross Profit Margin.